Model System Dynamics Model System Dynamics Perubahan Stock Polusi CO2 Akibat Emisi dan Absorbent Di Indonesia: Memahami Hubungan Sebab Akibat dalam Polusi co2 - Wibisono, Naufal; Sukendro, Achmed; Heridadi Heridadi; Widodo, Pujo (CV. AFDIFAL MAJU BERKAH, 2024)
Air pollution, including CO2 pollution, is a serious issue worldwide, including in Indonesia. This CO2 pollution can impact public health and the environment. In the context of economic development, activities in Indonesia are increasing, leading to higher CO2 emissions. The highest CO2 emissions come from deforestation, large-scale peatland fires, and, to a lesser extent, burning fossil fuels for energy. This research focuses on a simple System Dynamics model approach to understand the cause-and-effect relationship of changes in CO2 pollution stocks concerning emissions and absorption in Indonesia. The method used in this study is qualitative based on system dynamics. System dynamics is a method that can be used to create structures, predict behavior, and provide feedback. The System Dynamics model uses Powersim Studio 10 Express, covering the research period from 2020 to 2040. The results of the system dynamics model show two structures related to CO2 pollution stocks: a positive feedback (reinforcing loop) from CO2 emissions and a negative feedback (balancing loop) from CO2 absorbent. The behavior of the model is exponential growth, it’s also considered valid due to simulation results based on real data processing and statistical analysis, yielding an Average Means Error (AME) of 0.56%.